Advanced nondestructive evaluation I : proceedings of the 1st International Conference on Advanced Nondestructive Testing, Jeju Island, Korea, 7-9 November 2005 - Lee, Seung-Seok (Trans Tech Publications, 2006)
The papers which make up this volume reflect the very diverse nature of nondestructive evaluation; covering as they do topics ranging from traditional NDE to newly developing NDE methods such as structural health monitoring; where nondestructive technologies are rapidly progressing by integrating emerging technologies from various fields. The collection is divided into twenty-seven chapters: Modeling and Simulation, New Methods and Devices, Optical Methods, Micro-Sensors and MEMS, Smart Structures & Systems, Health Monitoring of Structures, NDT for Infrastructures, NDT in the Nuclear Industry,
Keywords: Materials science -- Congresses.; Nondestructive testing -- Congresses.; elektronické knihy; electronic books